Pengembangan Bahan Ajar Ekonomi Terintegrasi Nilai Islam dengan Model Pembelajaran Contextual Teaching and Learning (CTL) - Khadijah, Siti; Arwansyah, Arwansyah; Rozaini, Noni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Madrasah graduates are expected to have intellectual abilities based on religious values ​​to improve life skills. The importance of general lessons being integrated with Islamic values ​​by connecting them with real world life. Providing modules that are integrated with Islamic values ​​is very necessary. The aim of this research is to develop teaching materials that are integrated with Islamic values ​​using the Contextual Teaching and Learning (CTL) learning model, analyzing the feasibility of teaching materials from the assessment of material expert validation results, media and learning design, subject teacher responses and also looking at student responses through individual tests and small group tests as well as analyzing students' responses to the products developed which focus on the economic subject matter Accounting as an Accounting Information System in class XII IPS 2 in semester V. The model used in this research is ADDIE (Analysis, Design, Development , Implementation, and Evaluation) proposed by Branch. The subjects in this research were students in class XII IPS 2 with a sample size of 30 students. The results of this research are that teaching materials are considered appropriate with an average percentage of 85,78% were in the "Very Eligible" criteria. Student responses with an average percentage of 89.11% were in the "Very Eligible" criteria